Analisis Financial Crunch Perbankan Syariah di Indonesia Pada Saat Krisis Keuangan Global 2008 - , M. SOBAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Global financial crisis that happened in 2008 has affected banking world in Indonesia. This causes bank conducting more selective credit policy so that it can emerge credit crunch phenomenon. Credit crunch also possible happen in sharia banking that often called as financial crunch. This can be proven with rapid third party capital growth but do not be accompanied by significant credit growth. This study aims to analysis whether financial crunch has happened in sharia banking in Indonesia when global financial crisis in 2008 and to analysis affecting factors of credit in sharia banking industry in Indonesia. This study result generally shows that financial crunch do not happen in Indonesian sharia banking. It means credit delivery of sharia banking is consistent between prior and after global financial crisis in 2008. Several factors that affect on credit delivery in sharia banking are third party capital collection, CAR, NPF, GDP and SWBI/SBIS. Third party capital, capital adequacy ratio (CAR) have positive significant effect on sharia banking credit delivery, whereas non performing finance (NPF), gross domestic product and SWBI/SBIS have negative effect on sharia banking credit. Keywords: credit crunch, financial crunch CAR, NPF, GDP and SWBI/SBIS